Textbook of Hernia - Hope, William W.; Cobb, William S.; Adrales, Gina L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This textbook provides a comprehensive, state-of-the art review of the field of hernia surgery, and will serve as a valuable resource for clinicians, surgeons and researchers with an interest in both inguinal and ventral/incisional hernia. This book provides an overview of the current understanding of the biologic basis of hernia formation as well as laying the foundation for the importance of hernia research and evaluating outcomes in hernia repair. Diagnosis and management strategies for inguinal and ventral hernia are discussed in detail with separate techniques sections for the most widely used procedures in this field as well as emerging technologies such a robotic and single incision surgery. Pertinent associated topics to inguinal hernia surgery such as chronic groin and athletic pubalgia are covered in detail. For incisional hernias, associated topics such as hernia prevention and enhanced recovery protocols are discussed. For both inguinal and ventral/incisional hernias mesh choices and available mesh technologies are discussed in detail as this remains an often confusing matter for the general surgery. When appropriate, chapters to highlight controversies in care are featured such as the use of synthetic mesh in contaminated surgery and laparoscopic closure of defects in laparoscopic ventral hernia repair. Current recommendations and outcomes data are highlighted when available for each technique. Textbook of Surgery will serve as a very useful resource for physicians and researchers dealing with, and interested in, abdominal wall hernias. It will provide a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts.
Biology of hernia formation -- Epidemiology/Importance of hernia research -- Evaluating evidence and outcomes in Hernia repair -- Inguinal hernia -- Epidemiology of inguinal hernia -- Diagnostic options for inguinal hernia repair -- Watchful waiting in inguinal hernia repair -- Mesh options for inguinal hernia repair -- Anesthetic considerations for inguinal hernia repair -- Overview of hernia techniques -- Shouldice technique -- Tissue based repairs -- Lichtenstein repair -- Open posterior approaches -- Laparoscopic repair (TEP) -- Laparoscopic repair (TAPP) -- Emerging technology: Robotic inguinal hernia repair -- Emerging technology: SILS inguinal hernia repair -- Overview of chronic groin pain -- Preventive strategies for chronic groin pain -- Diagnostic evaluations for chronic groin pain -- Pain mapping for chronic groin pain -- Non-surgical options for management of chronic groin pain -- Surgical options for management of chronic groin pain -- Emergency and Atypical Hernias: Management of Incarcerated/Strangulated inguinal Hernias -- Emergency and Atypical Hernias: Management of Femoral/Obturator hernias -- Incisional and ventral hernias -- Introduction/Epidemiology -- Hernia prevention/Techniques for laparotomy closure -- The use of prophylactic mesh in laparotomy closure and ostomy creation -- Preoperative prepration/Enhanced recovery protocols for incisional/ventral hernias -- Mesh options for incisional/ventral hernias -- Overview of Techniques in incisional and ventral hernias -- Laparoscopic approaches to incisional/ventral hernias -- Open approaches: Onlay techniques -- Open approaches: Retrorectus/TAR techniques -- Open approaches: Anterior component separation techniques -- Open approaches: Minimally invasive techniques for component separation -- Open approaches: Alternative methods for component separation -- Emerging technology: Robotic IPOM -- Emerging technology: Robotic retromuscular repair -- Emerging technology: SILS lap VHR -- Controversies in incisional/ventral hernia: Laparoscopic closure of hernia defects -- Controversies in incisional/ventral hernia: Mesh choices in contaminated cases -- Umbilical hernia repair -- Complex and atypical incisional/ventral hernia: Management of incarcerated/strangulated hernias -- Complex and atypical incisional/ventral hernia: Aytpical henrias: Subxiphoid/Suprapubic/Lumbar/Flank hernias -- Complex and atypical incisional/ventral hernia: Management of diastasis Recti -- Complex and atypical incisional/ventral hernia: Management Dehiscence/Evisciration -- Complex and atypical incisional/ventral hernia: Abdominal compartment syndrome and management of the open abdomen -- Complex and atypical incisional/ventral hernia: Parastomal hernia repair -- Complex and atypical incisional/ventral hernia: Management of mesh infections and enterocutaneous fistulas -- Complex and atypical incisional/ventral hernia: Use of preoperative progressive pneumoperitoneum in complex abdominal wall hernias -- Complex and atypical incisional/ventral hernia: The use of Botox for chemical component separation -- Athletic pubalgia -- Overview of problem/epidemiology -- Diagnostic evaluations -- Non-surgical treatment options in Athletic pubalgia -- Surgical treatment options in Athletic pubalgia.
Keywords: Medicine; Abdominal surgery; Surgery; Medicine & Public Health; General Surgery; Abdominal surgery